Factors contributing to the usage of pocket parks―a review of the evidence - Balai Kerishnan, Praveena; Maruthaveeran, Sreetheran (Elsevier, 2021)
This paper presents a summary of empirical evidence drawn from a literature review on the factors contributing to people using the pocket parks. Initial findings indicate that pocket parks play a significant role by providing access to nature for individuals living in urban areas. This paper provides an evidence-based approach to the usage and benefits of pocket parks by applying the SE-Model approach. This review includes 15 papers on pocket parks, obtained from electronic journal databases such as Scopus, Science Direct, Springer Link, SAGE Journals and Google Scholar sort by relevance containing key words such as pocket parks, vest-pocket parks, small public urban green space, small urban parks, use as well as usage of pocket parks. Selection was restricted to peer-reviewed publications related to pocket parks usage. The authors analysed these literatures for its sample characteristics, data collection, sampling method, data analysis and the main study finding. This review reveals an increase in research on the usage of pocket parks published in peer-reviewed journals in the recent years and a strong geographic bias. The selected studies have consistently reported on the importance of pocket parks for mental well-being, predominantly, followed by social benefits, however limited study approached the potential of pocket parks for physical activities. Physical components (green ground cover, bushes, trees, flower beds, water features) and Perceived Environment (preference for greener view; calm atmosphere; safety) are mostly reported to be highly associated with human health.